An Analytic Hierarchy Process Based Approach for Evaluating Renewable Energy Sources - Robles Algarin, Carlos Arturo; Polo Llanos, Aura; Ospino Castro, Adalberto (International Journal of Energy Economics and Policy, 2017)
Decision-making in energy planning can be approached as a problem of multicriteria decision analysis in which different types of factors are involved. This task must take into account several aspects due to the increasing complexity of social, technological and economic factors. In this context, this paper uses the Analytic Hierarchy Process (AHP) to prioritize a set of criteria, subcriteria and alternatives as a support for decision-making in the process of energy planning with renewable energies for rural areas in the Caribbean region of Colombia. Based on the participation of experts, 5 criteria, 20 subcriteria and 4 alternatives were defined. Using the AHP, the same group of experts was consulted in order to prioritize all aspects. The results showed that the most relevant criteria were the technical with 24.7%. Next were environmental (21.7%), social (19.6%), economic (17.8%) and risk (16.3%). The best renewable energy alternative was solar with 45.3%. Keywords: Renewable Energy, Energy Planning, Analytic Hierarchy Process JEL Classifications: Q20, Q42, D70